2020
DOI: 10.3991/ijet.v15i24.19309
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors in the Perception of Cyberbullying in Victimized Adolescents: Psychoeducational Implications

Abstract: The knowledge of the perceptual structure that victims have of the cyberbullying phenome-non favors the adjustment of prevention and intervention programs. However, there are few studies that try to find out what are the factors that influence the construction of a certain perceptual structure on cyberbullying, let alone those that focus on a population such as victimized adolescents. This paper aims to know the perceptual structure that victimized adolescents have about cyberbullying, as well as the factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Within the research community, cyberbullying has garnered diverse interpretations and consequently, different meanings (Langos, 2012;Redmond, Lock and Smart, 2020). Building on traditional bullying, as measured by the Olwens Bullying questionnaire, studies have revealed that respondents often equate cyberbullying to acts that involve the internet and technology (Dennehy et al, 2020;Fernández-Antelo, Cuadrado-Gordillo and Parrà, 2020). For example, the item "somebody used the internet or a cellphone to harm/offend me" has been regarded as an act of cyberbullying.…”
Section: Cyberbullying Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the research community, cyberbullying has garnered diverse interpretations and consequently, different meanings (Langos, 2012;Redmond, Lock and Smart, 2020). Building on traditional bullying, as measured by the Olwens Bullying questionnaire, studies have revealed that respondents often equate cyberbullying to acts that involve the internet and technology (Dennehy et al, 2020;Fernández-Antelo, Cuadrado-Gordillo and Parrà, 2020). For example, the item "somebody used the internet or a cellphone to harm/offend me" has been regarded as an act of cyberbullying.…”
Section: Cyberbullying Dimensionsmentioning
confidence: 99%
“…These attributes, further classed as Category-1, provide a baseline for cyberbullying identification within the cyberbullying conceptual framework. Whilst the identification of cyberbullying act, specifically from the student's perspective, presents a means for cyberbullying construct development (Dennehy et al, 2020;Fernández-Antelo, Cuadrado-Gordillo and Parrà, 2020), the content presented in the conceptual framework lacks useful composition that can be used as indicators or precursors. Cyber bully indicator can be defined within a context or in perspective: the victim, perpetrator, or collaborators, for example.…”
Section: Cyberbullying Dimensionsmentioning
confidence: 99%
“…Another factor related to the 'forms of social relationship' characteristic of adolescents associated with playful themes. Under this label adoles-cents includes verbal aggressions such as insults, spreading false rumours, or visual abuse such as the publication and dissemination of images or videos [13] According to Kim [14] spending more time on the computer is negatively related to mental health in the following year. Also, the use of digitals tools has a direct influence on memorization as a learning process and it seems negative when this duration of use exceeds 2 hours [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given these circumstances, understanding these possible risk factors constitutes an important step towards addressing and developing the acquisition of the social skills necessary to deal with these issues [97]. As some studies indicate, the acquisition and development of social skills in the immigrant population facilitates greater inclusion in the educational context, increases their social wellbeing and thereby reduces intercultural social conflicts [98].…”
Section: Online Teaching and Its Inference In The Social Problems Of Intercultural Studentsmentioning
confidence: 99%